Powder and High-Solid Coatings - Rossi, Stefano (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This volume illustrates some of the most innovative aspects of organic coatings designed not only to protect against corrosion but also to obtain smart coatings. Both modification of the composition of organic coatings and performance evaluation techniques are presented.